Strontium isotopic aspects of Paranthropus robustus teeth; implications for habitat, residence, and growth. Issue 114 (January 2018) - Sillen, Andrew; Balter, Vincent
Abstract: The strontium isotopic ratio 87 Sr/ 86 Sr has been studied in the Sterkfontein Valley of South Africa to infer both habitat usage and residence for a number of early hominins. This paper examines the existing 87 Sr/ 86 Sr data collectively derived from three studies of Paranthropus robustus teeth with the aim of exploring whether the dataset as a whole may provide deeper insight into habitat, mobility, and growth for this species. 87 Sr/ 86 Sr from seven Swartkrans Member I third molars varies in a well defined narrow range, and while some canines were consistent with this range, a number of P. robustus canines and first and second molars were not, and therefore represent individuals who had arrived from other localities. A first and third molar 87 Sr/ 86 Sr was found to differ in TM1517c, the holotype P. robustus specimen from Kromdraai, suggesting this individual had moved to the locality sometime after the first molar and before the third molar had completely mineralized. While early forming teeth vary widely, the relatively low variation and absence of exogenous 87 Sr/ 86 Sr in third molars suggest that these teeth mineralized relatively late when compared to life history events bearing on higher primate residence patterns. The implications for further study of habitat, residence, and growth are discussed.